A review on integrated design and application of stimuli-responsive ZIF-8 metal-organic frameworks for breast cancer theranostics - Jha A.K.; Arora S.; Sahu R.C.; Kumar D.; Singh S.; Agrawal A.K. (My University, 2025)
Breast cancer continues to be a predominant cause of death among women globally, necessitating the development of more effective and targeted treatment strategies. While current therapies have shown efficacy, they are often associated with notable adverse effects and inadequate tumor targeting. This review explores the potential of stimuli-responsive zeolitic imidazole framework-8 (ZIF-8) metal-organic frameworks (MOFs) in the treatment of breast cancer. Composed of zinc ions and imidazolate linkers, ZIF-8’s structure offers pH-sensitive degradation, making it ideal for precise medication delivery in the acidic tumor microenvironment. We investigate various synthesis methods and emphasize the advantages of ZIF-8 in enhancing drug bioavailability and precision targeting. The stimuli-responsive properties of ZIF-8 MOFs—such as responsiveness to pH, light, temperature, ultrasound, redox conditions, and enzymes—enable controlled and site-specific drug release. Furthermore, we examine the integration of ZIF-8 MOFs with existing breast cancer therapies and their applications in diagnostics and imaging. Consideration is also given to the biocompatibility of ZIF-8 to ensure safe and effective clinical use. This review article offers a comprehensive analysis of the function of stimuli-responsive ZIF-8 MOFs in transforming breast cancer therapy and facilitating novel treatment approaches. © 2025 The Authors